Hukum Melihat Handphone yang Sedang Digunakan oleh Orang Lain Tanpa Izin: Perspektif Hukum Islam - Sinaga, Ali Imran; Anwar, Wan Tasya Luthfiah; Rahmadani, Rahmadani; Rahmat, Ilham; Handayani, Irma (VISA: Journal of Vision and Ideas, 2025)
This research aims to analyze legal issues that arise as a result of the act of viewing a cellphone that is being used by another person without permission, seen from the perspective of Islamic law. In this digital era, the use of communication devices, such as cellphones, is increasing, and unconscious privacy violations often occur, one of which is accessing other people's personal information without permission. In this study, the author examines the basic principles of Islamic law relating to privacy, individual rights, and limits in social interaction, especially those relating to the protection of one's honor and privacy. The approach used in this research is normative analysis by referring to Islamic legal texts, both those originating from the Al-Qur'an, Hadith, and fiqh rules. The research results show that the act of looking at another person's cellphone without permission can be seen as a violation of a person's right to privacy, which in Islamic law is included in the category of impermissible actions, because it can damage an individual's honor and dignity. Apart from that, Islamic law also emphasizes the importance of etiquette and mutual respect for each other, so these actions should be avoided to maintain social harmony. Thus, this research provides an understanding of how Islamic law views and regulates privacy and the boundaries of interacting with other people in a modern context.